Investment Cash Flow Evaluation Techniques: Myths and Realities - Solé Madrigal, Roberto (2011)
Being that the main objective of project evaluation is to compare the projectedbenefits (net savings) with their corresponding investment cash flow, during the last decades it has become increasingly imperious to count on consistent evaluation methodologies that allow the financial evaluator to clearly interpret them for a correctdecision Administrators, financial experts and economists have made efforts to develop and/or perfect these methodologies, but many of those efforts have been in vain, because it has been ignored that some of them come from purely mathematical structures, whose financial interpretations lack any sense, as is demonstrated in thisinvestigation As the reader will see along this article, and although some techniques presents some best virtues than the others evaluating returns in the investment cash flows or in the projects, is clear that no exist a unique technique capable of resolve satisfactorily all problems that occur in practice, which it will be shown through approaches mathematical-financial Certainly some metrics are complementary with each other, and must be used in the context of the project that is being measured.